2015
DOI: 10.1016/j.math.2014.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Cervical kinematic training with and without interactive VR training for chronic neck pain – a randomized clinical trial

Abstract: Impairments in cervical kinematics are common in patients with neck pain. A virtual reality (VR) device has potential to be effective in the management of these impairments. The objective of this study was to investigate the effect of kinematic training (KT) with and without the use of an interactive VR device. In this assessorblinded, allocation-concealed pilot clinical trial, 32 participants with chronic neck pain were randomised into the KT or kinematic plus VR training (KTVR) group. Both groups completed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
124
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(133 citation statements)
references
References 50 publications
6
124
0
3
Order By: Relevance
“…As such, impaired neck kinematics should be addressed clinically. In a recent pilot trial, we demonstrated the potential value of kinematic training using this system with positive results (Sarig-Bahat et al , 2014). The results of this current study confirm the need for further research in this area and the establishment of appropriate classification criteria for kinematic assessment and treatment…”
Section: Accepted Manuscriptsupporting
confidence: 75%
“…As such, impaired neck kinematics should be addressed clinically. In a recent pilot trial, we demonstrated the potential value of kinematic training using this system with positive results (Sarig-Bahat et al , 2014). The results of this current study confirm the need for further research in this area and the establishment of appropriate classification criteria for kinematic assessment and treatment…”
Section: Accepted Manuscriptsupporting
confidence: 75%
“…VR has been used as a distraction tool for pain management. Different forms of VR distractions have been used for burn wound pain [ 44 - 47 ], phantom limb pain [ 48 , 49 ], cold pressor pain [ 50 , 51 ], dental pain [ 52 , 53 ], neck pain [ 54 , 55 ], back pain [ 56 ], and cystoscopy [ 57 ] as well as for the assessment of analgesia [ 58 - 60 ] and kinesiophobia [ 56 , 61 ]. Distractions ranged from coastal walks [ 52 ] and target-aiming tasks [ 61 ] to a Sonic the Hedgehog Nintendo video game [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is potentially important for the progression of this device for use in neck rehabilitation as recently this system was used in a trial in 32 patients with chronic neck pain (Sarig Bahat et al 2015). Four out of 40 eligible patients withdrew from the study due to side effects (Sarig Bahat et al 2015). The information gained from the current study especially regarding VR exposure time may help to limit the degree of SS in the future.…”
Section: Duration Of Vr Immersionmentioning
confidence: 92%
“…Future research that aims to determine the optimal exposure time for the neck VR and any benefit of modifying the ROM module as suggested above to reduce exposure time should be explored further. This is potentially important for the progression of this device for use in neck rehabilitation as recently this system was used in a trial in 32 patients with chronic neck pain (Sarig Bahat et al 2015). Four out of 40 eligible patients withdrew from the study due to side effects (Sarig Bahat et al 2015).…”
Section: Duration Of Vr Immersionmentioning
confidence: 99%